STUDI LITERATUR : PERBANDINGAN PENERAPAN TEKNIK TEPID WATER SPONGE DAN KOMPRES HANGAT UNTUK MENURUNKAN SUHU TUBUH PADA ANAK YANG MENGALAMI KEJANG DEMAM - Nova Ari Pangesti; Bayu Krisna Anggara Mukti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Background: The prevalence of febrile seizures in children under five years of age occurs every year in America, almost as much as 1.5 million and mostly more common in children aged 6 to 36 months (2 years), especially at 18 months of age. The specific symptom of a febrile seizure is hyperthermia. With increased metabolism in the body, oxygen supply to the brain decreases. In sensitive children, febrile seizures will occur. If not resolved immediately, febrile seizures will result in an increase in intra-cranial pressure (ICT) which affects the disruption of nutrient supply (perfusion) to the tissues throughout the body so that growth and development disorders can occur. Purpose: This literature review aims to compare the application of the tepid water sponge technique and warm compresses to reduce body temperature in children with fever. Methods: The method used was a literature review, which collected and analyzed research articles on the application of the Tepid Water Sponge and Warm Compress techniques. Search for articles is carried out through (databases) such as Google scholar or Google scholar using keywords such as